Dual HLA B*42 and B*81-reactive T cell receptors recognize more diverse HIV-1 Gag escape variants - Funsho Ogunshola (Nature Portfolio, 2018)
Closely related HLA alleles presenting similar HIV-1 epitopes can be associated with variable clinical outcome. Here the authors report their findings on CD8+ T cell responses to the HIV-1 Gag-p24 TL9 immunodominant epitope in the context of closely related protective and less protective HLA alleles, and their differential effect on viral control